Capacity Building for Kampung Wisata Tenun Khatulistiwa’s Enterpreneurs through Digital Marketing, CHSE and Destination Exploration Training in the New Normal Era - Ul Qadri; Rudy Tandra; Tri Wahyuarini; Evi Sofiana; Sulaiman Sulaiman; Era Prestoroika (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Kampung Wisata Tenun Khatulistiwa which was inaugurated by the Mayor of Pontianak in 2018 is one of the leading tours of Pontianak City. Currently, Kampung Wisata Tenun Khatulistiwa, which has become an icon of Pontianak City, has a gallery of attractions and weaving products called the Weaving Production House. The existence of this gallery brings through domestic and foreign communities to see the activities and works of weaving directly and freely. The implementation of Cleanliness, Health, Safety and Environmental Sustainability (CHSE) in an exhibition activity is an adaptation of changes in behavior or habits (new normal) that must be carried out by exhibition organizers to meet the needs of tourists such as clean, healthy, safe and environmentally friendly tourism products and services during the COVID-19 pandemic. The new normal condition, which is currently in the era of the industrial revolution 4.0, has also triggered more rapid development in the digital sector or digital economy. MSME actors must be able to communicate and utilize various technologies to reach the market. Digital marketing, CHSE and exploration training were community service activities that aim to increase the capacity of Kampung Wisata Tenun Khatulistiwa entrepreneurs in the new normal era. Evaluation of community service activities can be seen from the modification of one area of the village by the local community into an instagrammable spot and a number of photos of visitors that were captured while trying the attraction of weaving with traditional product tools